2017
DOI: 10.1177/0954411917737584
|View full text |Cite
|
Sign up to set email alerts
|

State-of-the-art robotic devices for ankle rehabilitation: Mechanism and control review

Abstract: There is an increasing research interest in exploring use of robotic devices for the physical therapy of patients suffering from stroke and spinal cord injuries. Rehabilitation of patients suffering from ankle joint dysfunctions such as drop foot is vital and therefore has called for the development of newer robotic devices. Several robotic orthoses and parallel ankle robots have been developed during the last two decades to augment the conventional ankle physical therapy of patients. A comprehensive review of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 57 publications
(200 reference statements)
0
27
0
1
Order By: Relevance
“…Wearable ankle rehabilitation robots known as a powered ankle exoskeleton or a powered ankle-foot orthoses are being developed (Hussain et al, 2017). In accordance with the FDA's definition, a robotic exoskeleton is a prescription device which consists of external and powered orthosis for medicine, and which is attached to a person's paralyzed or weakened limbs to assist with ambulation' (Food and Drug Administration, HHS 2015) (Contreras-Vidal et al, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…Wearable ankle rehabilitation robots known as a powered ankle exoskeleton or a powered ankle-foot orthoses are being developed (Hussain et al, 2017). In accordance with the FDA's definition, a robotic exoskeleton is a prescription device which consists of external and powered orthosis for medicine, and which is attached to a person's paralyzed or weakened limbs to assist with ambulation' (Food and Drug Administration, HHS 2015) (Contreras-Vidal et al, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…However, a force sensor offers additional information such as the GRF, which can be used to estimate the desired joint torque [75,77]. When using a GRF sensor, the position of the sensor should be especially considered for obtaining the reading from the heel contact force [12]. Thus, it can be concluded that certain factors should be considered when choosing between an adaptive and fixed output reference for an AFO.…”
Section: Output Reference: Fixed Versus Adaptivementioning
confidence: 99%
“…Nowadays, the ancillary equipment is enhanced with robotic technologies, such as an orthosis and exoskeleton, to make it more sophisticated for rehabilitation sessions. Not only can the bio-physical data be monitored, but the training process can also be automated with the addition of robotic technology with an emphasis on assist-as-needed training [12]. Therefore, it is now possible to replace most of the work of therapists in conventional training through the use of robotics-enhanced ancillary equipment.…”
Section: Introductionmentioning
confidence: 99%
“…During the conventional manually physiotherapy, human ankle complex (HAC) is moved by a physical therapist with its range of motion (ROM). However, it possesses many limitations such as, the duration inconsistency and frequency indetermination of the treatment procedures, the physical demand, and experience requirement of the therapist, and the subjective evaluation of the therapeutic results (Meng et al, 2015;Hussain et al, 2017). In view of this situation, to provide high-quality rehabilitation treatment with repetitive sessions, quantitative measurements, scientifical therapy, and systematic operation, robot-assisted rehabilitation has become a field that receives more, and more research attention.…”
Section: Introductionmentioning
confidence: 99%